Too many migrants? understanding xeno-otherism in Singapore. - Wong, Gwendolyn Kai Liang. (2013)
Time and again, the Singapore State has brought up the need for foreign migrants to ease the problems associated with demographic changes in Singapore. These include low fertility rates and an imminent aging population that will affect Singapore’s progress in the world economy. As such, the Population White Paper was recently introduced to deal with these demographic changes. However, this resulted in a furore, with 5000 citizens heading to Hong Lim Park to stage a protest. This also saw a rise in xeno-otherist sentiments in Singapore. This sense of xeno-otherism present needs to be understood for what it is, in order for it to be tackled. Is this sense of xeno-otherism truly a dislike of foreign migrants or does it have to do with Singaporeans’ discontent towards the sociopolitical landscape in Singapore?